Use of Arabic in a Gender Perspective - Rifki Zaitul Ikhlas; Tika Muzayanah; Syaiful Mustofa (al-Afkar, Journal For Islamic Studies, 2024)
Arabic is able to influence the psychology of its users. This psychology can shape daily positive behavior, and this behavior will strengthen a person's masculine and feminine attitudes. This masculine and feminine can be seen from the aspects of intonation, use of words and sentences used. This research aims to analyze the use of Arabic in user psychology in gender perception. This research uses a qualitative approach using the case study method of foreign students studying at the Maulana Malik Ibrahim State Islamic University, Malang. Data collection techniques through observation and interviews.  Data analysis through data collection, data presentation, and conclusions. Validation of data using triangulation. The results of this research show that the use of Arabic from a gender perspective can influence the psychology of its users. This is proven through language structure, appearance and behavior. Language structures include high phonology and low language, word change morphology, and semantics explaining muannats-mudzakkar, mufrad, mutsanna, jama’. Appearances include masculine and feminine. Men's language behavior tends to use shorter and more assertive language, while women tend to be more wordy in communication.  The results of this research are expected to provide information as a basis for consideration, support and contribution of thought for future researchers.